Normal mouse intestinal mucus release requires cystic fibrosis transmembrane regulator–dependent bicarbonate secretion - Garcia, Mary Abigail S.; Yang, Ning; Quinton, Paul M. (The Journal of Clinical Investigation, 2009)
The mechanisms underlying mucus-associated pathologies in cystic fibrosis (CF) remain obscure. However, recent studies indicate that CF transmembrane conductance regulator (CFTR) is required for bicarbonate (HCO3–) transport and that HCO3– is critical for normal mucus formation. We therefore investigated the role of HCO3– in mucus secretion using mouse small intestine segments ex vivo. Basal rates of mucus release in the presence or absence of HCO3– were similar. However, in the absence of HCO3–, mucus release stimulated by either PGE2 or 5-hydroxytryptamine (5-HT) was approximately half that stimulated by these molecules in the presence of HCO3–. Inhibition of HCO3– and fluid transport markedly reduced stimulated mucus release. However, neither absence of HCO3– nor inhibition of HCO3– transport affected fluid secretion rates, indicating that the effect of HCO3– removal on mucus release was not due to decreased fluid secretion. In a mouse model of CF (mice homozygous for the most common human CFTR mutation), intestinal mucus release was minimal when stimulated with either PGE2 or 5-HT in the presence or absence of HCO3–. These data suggest that normal mucus release requires concurrent HCO3– secretion and that the characteristically aggregated mucus observed in mucin-secreting organs in individuals with CF may be a consequence of defective HCO3– transport.